Understanding Students' Learning Experiences Through Journal Writing - Maharsi, Ista (English Education Department, Universitas Islam Indonesia, 2010)
This paper will make attempts to understand students learning experiences through journal writing. How students feel about the subject including materials, lecturers, learning activities, how they experience the learning processes, and identify their difficulties are several issues that will be discussed. Various significant issues found in students' journals will also be used to analyze and evaluate classroom activities.This study is conducted in a particular context of class room first semester undergraduate students of Accounting Department at the Faculty of Economics Universitas Islam Indonesia. The students are obliged to take Output Character Building Program (CCD) which is aimed to prepare new students to readily involve in academic environment and tasks. Data were collected from eight students' journals from two different classes and teacher's journal. They were required to write daily-basis reflective journal at the end of every meeting which is then analyzed to reveal significant issues addressed by students.The result of the class observation shows that regular journal writing function as a tool of effective communication between students-teachers, a media for students to express their feeling towards learning, promote better teacher-student rapport, and good feedback from students for the betterment of teaching and learning process. At further stages, the findings could be used to evaluate and develop better program.